2021
DOI: 10.2147/jmdh.s316595
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Pharmaceutical Logistics System Implementation in Chagni Primary Hospital and Injibara General Hospital, Awi Zone, Ethiopia

Abstract: Background Integrated Pharmaceutical Logistics System is the primary mechanism through which all public health facilities in Ethiopia get essential pharmaceutical products from their main supplier. Pharmaceuticals should be managed appropriately because they are part of the link between the patient and health services and account for up to half of the healthcare budget. This study aimed to assess the status of Integrated Pharmaceutical Logistics System implementation at both Chagni Primary Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Likewise, a study in Dessie found that oral rehydration salt had the least frequently updated bin-card [ 3 ]. Bin-cards play a crucial role in drug management by providing essential information on stock balance, receipt and issue quantities, and expiration dates [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, a study in Dessie found that oral rehydration salt had the least frequently updated bin-card [ 3 ]. Bin-cards play a crucial role in drug management by providing essential information on stock balance, receipt and issue quantities, and expiration dates [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SOP for IPLS recommends that health facilities should complete RRF as per their review period and collect products from the affiliated EPSA branch [ 10 , 22 ]. However, the results indicate that only 16.7% of the health facilities used RRF, while the majority used their own forms for reporting and requesting these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation